Rotary ultrasonic machining of difficult-to-machine materials: experimental and theoretical investigations - Fernando, Palamandadige (Kansas State University, 2020)
High-performance materials such as composite materials, metal alloys, and advanced ceramics are attractive to engineering applications in aerospace, automobile and sport industries. Materials with superior properties are often difficult-to-machine due to their high strength, high hardness, and high toughness, which make the cutting force and temperature at the cutting interface very high and result to a short tool life. This limits their market expansion due to the high cost of machining with current machining procedures. However, the demand for high-performance materials is increasing in certain industries such as aerospace and automotive. In addition to machining of high performance materials, some of the conventional materials such as rocks also can be categorized into difficult-to-machine materials. Some causes which made rock drilling complicated are expose to several rock types in a single drilling, an infinite variability of rock properties, relatively high hardness and high abrasiveness of rocks, friction between rock and tool, severe wear and damage to tools etc. Therefore, it is crucial to develop more cost-effective machining processes for difficult-to-machine materials. Rotary ultrasonic machining (RUM), a hybrid non-traditional machining process combining the material removal mechanisms of abrasive grinding and ultrasonic machining, has the potential for low-cost and high quality machining of difficult-to-machine materials. Researchers have shown that RUM can attain a higher material removal rate than both ultrasonic machining (USM) and grinding. RUM can also drill deep holes with high accuracy, improved surface finish, and low cutting force and torque. The objectives of this research are to investigate the relationships between input variables and output variables of RUM of difficult-to-machine materials, to study the measurement methods of ultrasonic vibration amplitude and the effects of tool natural frequency on ultrasonic vibration amplitude, and to model RUM of rocks. In this dissertation, research has been conducted by experimental, numerical, and theoretical investigations on output variables including cutting force, torque, surface roughness, edge chipping, and delamination. The goal of this research is to provide new knowledge based on machining difficult-to-machine materials on RUM in order to improve the quality of the machined holes while decreasing the machining cost and to study the effects of machining variables (feedrate, tool rotation speed, and ultrasonic power) and tool variables (abrasive size and concentration, tool diameter, and tool geometry) on output variables. This dissertation firstly provides the introduction to difficult-to-machine materials and rotary ultrasonic machining. After that Chapter 2 investigates the effects of input variables on cutting force, torque, and surface roughness, and study the effects of machining variables, tool end angle, and the use of a backing plate on the delamination of RUM of CFRP. Chapter 3 studies the comparison between intermittent RUM and continuous RUM when machining K9 glass from the perspectives of cutting force, surface roughness, and chipping size. Chapter 4 investigates the effects of input variables on cutting force, torque, surface roughness, and edge chipping of the RUM of basalt, travertine, and marble, and development of a mechanistic predictive cutting force model for RUM of rocks based on the ductile mode removal and brittle fracture mode removal of rock under the indentation of a single abrasive particle. Chapter 5 discusses the effects of tool natural frequency on ultrasonic vibration amplitude. Finally, conclusions and contributions on RUM drilling are discussed in Chapter 6.
Keywords: Rotary ultrasonic machining; Mechanistic cutting force model; Ductile and brittle removal; Delamination on CFRP drilling; Rock drilling; Tool natural frequency